2008
DOI: 10.1097/ajp.0b013e318156d90c
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect of Botulinum-toxin A on Postwhiplash Neck Pain

Abstract: Study results suggest that BTXA treatment has some efficacy when administered within 1 year of the WI. However, a large, well-designed clinical trial is needed to draw final conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…One aspect that makes it difficult to reproduce certain studies is that the specific muscles injected are not identified in the study reports [30, 31, 34, 37]. Other studies sometimes do not give a complete description; for example, Lew et al report that the trapezius, levator scapulae, splenius capitis, and other posterior neck muscles were injected [32].…”
Section: Resultsmentioning
confidence: 99%
“…One aspect that makes it difficult to reproduce certain studies is that the specific muscles injected are not identified in the study reports [30, 31, 34, 37]. Other studies sometimes do not give a complete description; for example, Lew et al report that the trapezius, levator scapulae, splenius capitis, and other posterior neck muscles were injected [32].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported that BoNT/A alleviated various kinds of pain [41][42][43][44]. It has been assumed from the rat model that an antinociceptive effect of BoNT/A may be derived from blockage of substance P or glutamate release [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, the other tennis elbow study by Hayton et al (2005) did not demonstrate the usefulness of BoNTA in reducing pain. In addition, BoN-TA did not significantly improve pain scores among the small number of shoulder pain and whiplash injury studies (Singh et al 2009;Braker et al 2008;Carroll et al 2008;Padberg et al 2007). Back pain was evaluated in one RCT in our systematic review (Foster et al 2001).…”
Section: Total (95% Ci)mentioning
confidence: 99%
“…The three studies all recruited patients with a history of a whiplash injury and subsequent localized neck pain (Braker et al 2008;Carroll et al 2008;Padberg et al 2007). However, the duration of symptoms prior to trial enrolment was not consistent among the studies, ranging from 2 weeks to a year.…”
Section: Whiplash Associated Disordermentioning
confidence: 99%